2016
DOI: 10.1016/j.bbadis.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

CYB5D2 displays tumor suppression activities towards cervical cancer

Abstract: Cervical cancer is caused by infections with human papillomaviruses (HPV) and genetic alternations in the cervical epithelium. While the former is well studied, the latter remains unclear. We report here that CYB5D2/Neuferricin possesses tumor suppressing activity towards cervical tumorigenesis. Ectopic expression of CYB5D2 did not affect HeLa cell proliferation and the cell's ability to form xenograft tumors, but significantly inhibited HeLa cell invasion in vitro and the cell-produced lung metastasis in NOD/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In addition, NR2F1, an orphan nuclear receptor, has been confirmed to induce quiescence of disseminated tumor cells 22 . It has also been reported that CYB5D2 possesses tumor-suppressing activity and significantly inhibits cell invasion in vitro and cell-produced lung metastasis in vivo 23 . Additionally, the homozygous loss-of- function germline mutation in the NTHL1 gene is related to a new subtype of base-excision repair-associated adenomatous polyposis and colorectal cancer 24 .…”
Section: Resultsmentioning
confidence: 94%
“…In addition, NR2F1, an orphan nuclear receptor, has been confirmed to induce quiescence of disseminated tumor cells 22 . It has also been reported that CYB5D2 possesses tumor-suppressing activity and significantly inhibits cell invasion in vitro and cell-produced lung metastasis in vivo 23 . Additionally, the homozygous loss-of- function germline mutation in the NTHL1 gene is related to a new subtype of base-excision repair-associated adenomatous polyposis and colorectal cancer 24 .…”
Section: Resultsmentioning
confidence: 94%
“…Built on the seminal detection of HPV16 DNA in 61.1% (11/18) of cervical cancers in 1983 [61], it became clear that infection by HPV is the primary etiology of cervix carcinoma, particularly with the high-risk HPV types 16 and 18 [62]. Besides HPV infection, alterations in cellular oncogenic events are also required for cervical cancer [63]. The integration of both HPV16 and HPV18 at the gene desert suggests that HPV coordinately affects oncogene alterations for cervical cancer formation [13,[64][65][66][67].…”
Section: Association Of the 8q2421 Gene Desert With Oncogenesismentioning
confidence: 99%
“…Despite considerable advances in understanding the molecular basis of abdominal and pelvic neoplasms, abdominal and pelvic cancers, such as colorectal cancer, prostate cancer and cervical cancer, remain the most common form of cancer leading tumor-related mortality globally [1]; [2]; [3]. Radiotherapy is a cornerstone of modern management of malignancies and, > 50% of patients with cancer receive this treatment at some point in the course of their disease [4].…”
Section: Introductionmentioning
confidence: 99%